Type and Abundance of Phytoplanktons and Absorptions of Ammonia on African Catfish (Clarias gariepenus) Cultivation, Differences of Stoking Density With Bioflok - Aris Tarkus; Saberina Hasibuan; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from march until April 2014 in fish Farming technologilaboratory of faculty of fisheries and marine science university of riau. This research purposes toknow type and abundance of phytoplanktons and absorption of ammonia on arican catfish(clarian gariepenus) cultivation, differences of stoking density with bioflok technique.Experimental metods using completely random design (RAL) with one factor and faour leveltritment, each treatment done in theree times deuteronomy. Stocking density on each treatmentbegins from 20 fishes in one place for P0 40 fishes for P1 60 fishes for P2 and 80 fishes for P3by administering molasses and for each place P1-P3 as probiotics 20cc. Best result of this reserchis solid stocking 80s with total abundance 16303 indl/L, it is supported by parameter of waterquality in each treatmant where water quality consist of : temperatur 27-320C, pH 7-7.9, DO1.55-3.03 (mg/L), CO2 7.13-15.31 mg/L, phosphat 0.6173-1.2978 (mg/L), nitrate 0.5854-10.4236 (mg/l) and total organic material of water is 12.331-15.441 (mg/l).Keywords: bioflok, the phytoplankton, the quality of water